2019
DOI: 10.3390/cancers11040523
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-Dependent Kinase 5 (CDK5)-Mediated Phosphorylation of Upstream Stimulatory Factor 2 (USF2) Contributes to Carcinogenesis

Abstract: The transcription factor USF2 is supposed to have an important role in tumor development. However, the regulatory mechanisms contributing to the function of USF2 are largely unknown. Cyclin-dependent kinase 5 (CDK5) seems to be of importance since high levels of CDK5 were found in different cancers associated with high USF2 expression. Here, we identified USF2 as a phosphorylation target of CDK5. USF2 is phosphorylated by CDK5 at two serine residues, serine 155 and serine 222. Further, phosphorylation of USF2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 61 publications
2
22
0
Order By: Relevance
“…The current observations are also supported by studies in which depolarization of mitochondria occurred when CDK5, a positive regulator of USF2 [ 26 ], was knocked out [ 27 ]. Further, knockout of CDK5 in MDA MB-231 and MCF-7 cells enhanced ROS formation via mitochondria [ 27 ] in line with our present results showing an increased ROS formation in USF2-deficient cells.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The current observations are also supported by studies in which depolarization of mitochondria occurred when CDK5, a positive regulator of USF2 [ 26 ], was knocked out [ 27 ]. Further, knockout of CDK5 in MDA MB-231 and MCF-7 cells enhanced ROS formation via mitochondria [ 27 ] in line with our present results showing an increased ROS formation in USF2-deficient cells.…”
Section: Discussionsupporting
confidence: 80%
“…gRNA-encoding oligonucleotides (Sigma-Aldrich) were cloned into the vector SpCas9(BB)-2A-GFP (PX458, Addgene plasmid ID 48138) using standard procedures as described [ 38 ]. The generation of the USF2 control and knockout cells via CRISPR-Cas9-mediated non-homologous end-joining (NHEJ) DNA repair and the screening of the clonal cell lines was performed as already described [ 26 , 39 ]. All primer sequences are listed in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…An increasing body of evidence supports that the cytoplasmic TF STAT3 is activated constitutively in a variety of cancers wherein it significantly affects the growth of tumors and facilitates metastasis [51,52]. USF2 is observed in various human cancers, plays important roles in embryogenesis, metabolism, and cancer development [53]. A previous study indicated that USF2 is associated with tumor grade and inversely with survival in Stage II colon cancers [54].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to proliferation, several studies reported that CDK5 plays a role in regulating cancer cell motility. Depending on the study, CDK5 was shown to promote migration of cancer cells by phosphorylating actin-binding/regulatory proteins such as caldesmon, talin, or FAK, phosphatidylinositol 4-phosphate 5-kinase type I γ (PIPKIγ90), PIKE-A, a transcription factor USF2, or to indirectly activate small GTP-ases RalA and RalB (11,50,51,(58)(59)(60)(61)(62)(63). In contrast, other authors concluded that CDK5 serves to inhibit cancer cell migration and to suppress metastasis by phosphorylating a tumor-suppressor DLC1, a scaffold protein muskelin, a transmembrane glycoprotein PDPN, an epigenetic regulator EZH2, or a protein phosphatase PP2A (64)(65)(66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%